The Implementation of CTL in Teaching English Vocabulary st SDN Gontara - Sartika Andi Patau (Sintuwu Maroso Journal of English Teaching, 2021)
CTL involves students totally in learning process. Students are motivated to be achieve to study the material learning suitable with the topic. Learning vocabulabulary in Elementary School must be used the suitable method or strategy, because it was the basis knowledge in learning English. The implementation of CTL help the students to memorizes many vocabulary. The teacher followed the flow of teaching and learning process using CTL method, they are constructivism, inquiry, questioning, learning community, modeling, reflection and authentic assessment. The result of test obtained that the using of CTL is effective in teaching vocabulary at fifth grade of SDN Gontara